2019
DOI: 10.7759/cureus.4897
|View full text |Cite
|
Sign up to set email alerts
|

Esthesioneuroblastoma: Summary of Single-center Experiences with Focus on Adjuvant Therapy and Overall Survival

Abstract: Esthesioneuroblastoma (ENB) is a rare malignant tumor of the nasal cavity. The genetic basis of its development is still under study and has not been fully delineated. It has varying symptoms depending on the lesion’s location within the nasal cavity. The most commonly used systems for such lesions are the Kadish staging and Haymes grading systems. The objectives are to review the most recent published literature evaluating the different treatments/ combination of treatment and assess the most appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…However, the efficacy of CT treatment on ONB patient outcomes is largely speculated [ 8 ]. Some retrospective studies have reported positive patient outcomes in response to CT [ 17 , 18 ], while others have observed that CT is associated with poor patient outcomes [ 19 , 20 , 21 ], In a recent epidemiological survey, CT treatment was associated with poor ONB patient outcomes and reduced survival [ 21 ]. However, the long-term effects associated with CT and other treatment modalities on patient age groups remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy of CT treatment on ONB patient outcomes is largely speculated [ 8 ]. Some retrospective studies have reported positive patient outcomes in response to CT [ 17 , 18 ], while others have observed that CT is associated with poor patient outcomes [ 19 , 20 , 21 ], In a recent epidemiological survey, CT treatment was associated with poor ONB patient outcomes and reduced survival [ 21 ]. However, the long-term effects associated with CT and other treatment modalities on patient age groups remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, small, low-grade tumors resected with negative margins can be managed without adjuvant radiation therapy; however, tumors with higher Hyam's grade or positive dura, olfactory bulb, and/or brain would typically be offered at least local radiation therapy. [38][39][40][41] If surgeons defer elective skull base dissection, approximately 12% of patients may be inadvertently downstaged, and adjuvant therapy may not be offered. Although neither the involvement of intracranial structure on imaging or pathology nor the specific treatment modalities were significant predictors of OS or DFS, 83% of our multicenter cohort did receive radiation therapy, which introduces potential selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…There are additional treatment implications to consider if surgeons decide to defer elective skull base resection, specifically regarding adjuvant therapy. Currently, small, low‐grade tumors resected with negative margins can be managed without adjuvant radiation therapy; however, tumors with higher Hyam's grade or positive dura, olfactory bulb, and/or brain would typically be offered at least local radiation therapy 38–41 . If surgeons defer elective skull base dissection, approximately 12% of patients may be inadvertently downstaged, and adjuvant therapy may not be offered.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 17 studies published from 1990 until 2019 showed that surgery and adjuvant radiation therapy provided the best overall survival and progression‐free survival especially in patients with high Kadish stage. The role of chemotherapy was not clear 6 . A recent review of 149 articles also suggested surgical resection followed by radiotherapy as the standard approach for higher‐grade tumors 7 …”
Section: Discussionmentioning
confidence: 99%
“…The role of chemotherapy was not clear. 6 A recent review of 149 articles also suggested surgical resection followed by radiotherapy as the standard approach for higher-grade tumors. 7 A beneficial role of chemotherapy in ONB has been suggested owing to its biological behavior similar to other chemosensitive neural crest tumors like high-grade neuroendocrine tumors.…”
Section: Casementioning
confidence: 99%